2001
DOI: 10.1542/peds.107.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Early Diagnosis of Cystic Fibrosis Through Neonatal Screening Prevents Severe Malnutrition and Improves Long-Term Growth

Abstract: Although the screened group had a higher proportion of patients with pancreatic insufficiency, their growth indices were significantly better than those of the control group during the 13-year follow-up evaluation and, therefore, this randomized clinical trial of early CF diagnosis must be interpreted as unequivocally positive. Our conclusions did not change when the height and weight data before 4 years of age for the controls detected by unblinding were included in the analysis. Also, comparison of growth ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
332
2
21

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 578 publications
(369 citation statements)
references
References 34 publications
(44 reference statements)
14
332
2
21
Order By: Relevance
“…2 The Cochrane review 4 found a second randomised controlled trial from the UK 5 that did not show a benefit to early diagnosis but is of interest that in the latter study, patients screened for CF were not all referred to a specialist centre for their care. Thus the criterion that appropriate treatment facilities should be in place postscreening was not met in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The Cochrane review 4 found a second randomised controlled trial from the UK 5 that did not show a benefit to early diagnosis but is of interest that in the latter study, patients screened for CF were not all referred to a specialist centre for their care. Thus the criterion that appropriate treatment facilities should be in place postscreening was not met in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It is presently unknown whether survival will improve further with the introduction of neonatal screening for cystic fibrosis in Scotland in 2002/3, because the impact of the CFTR mutation on the subsequent pattern and severity of symptoms experienced by the patient remains controversial. With respect to neonatal screening, Farrell's Wisconsin cohort has shown some patient benefits of screening through long-term surveillance 2 but the controversy will only be settled by long-term analysis of trends using CF Registries. The UK CF Database contains such a registry within one of its modules and aims to analyse the clinical details of every cystic fibrosis patient in the United Kingdom who attends a specialist CF centre.…”
Section: Introductionmentioning
confidence: 99%
“…2 However, only 1440 CF patients in Poland (of over 38 million inhabitants) were registered in Polish Cystic Fibrosis Registry (data from 30 September 2010). 3 According to the Wisconsin Cystic Fibrosis Neonatal Screening Study Group and others, 4,5 newborn screening for CF (NBS CF) provides an immediate and accurate diagnosis, often before the onset of clinical symptoms and is associated with significantly improved physical development and a lower prevalence of lung infections. Neonatal screening for CF has been widely implemented and accepted, however, ethical aspects with regard to possible benefits and risks are still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] In Paraná, the mean age at diagnosis of CF used to be 1.6 years. 3 With the advent of neonatal screening it is possible to confirm diagnosis during the second month of life.…”
Section: Discussionmentioning
confidence: 99%